2022
DOI: 10.1097/ta.0000000000003529
|View full text |Cite
|
Sign up to set email alerts
|

Length of stay and trauma center finances: A disparity of payer source at a Level I trauma center

Abstract: BACKGROUND:In an effort to reduce costs, hospitals focus efforts on reducing length of stay (LOS) and often benchmark LOS against the geometric LOS (GMLOS) as predicted by the assigned diagnosis-related group (DRG) used by the Centers for Medicare and Medicaid Services. The objective of this cross-sectional study was to evaluate the impact of exceeding GMLOS on hospital profit/loss with respect to payer source. METHODS:Contribution margin for each insured patient admitted to a Level I trauma center between Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A key issue in the current study is that over 95% of patients were either covered by public insurance, such as Medicaid/Medicare, or were uninsured 17 . Of particular note, Medicaid and Medicare relative to private payors generally contribute negative contribution margins for trauma centers, and overall lower reimbursement to health systems 46–48 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A key issue in the current study is that over 95% of patients were either covered by public insurance, such as Medicaid/Medicare, or were uninsured 17 . Of particular note, Medicaid and Medicare relative to private payors generally contribute negative contribution margins for trauma centers, and overall lower reimbursement to health systems 46–48 …”
Section: Discussionmentioning
confidence: 93%
“…17 Of particular note, Medicaid and Medicare relative to private payors generally contribute negative contribution margins for trauma centers, and overall lower reimbursement to health systems. [46][47][48] The investigation is novel in its use of EDIE data which provides 5-year population-level follow-up ED and inpatient utilization data for the intent-to-treat sample. The use of EDIE allows for consolidation of emergency and inpatient utilization from all regional health care facilities in Washington State.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the use of TXA in THA for PWH may alleviate the economic burden on patients and potentially reduce the financial burden on the government. Studies have indicated that reducing hospitalization duration can alleviate the economic burden on patients 35 . Additionally, research has shown that reducing the hospitalization duration for elderly patients can lower overall economic costs 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that reducing hospitalization duration can alleviate the economic burden on patients. 35 Additionally, research has shown that reducing the hospitalization duration for elderly patients can lower overall economic costs. 36 The mean values for length of stay and hospitalization costs were lower in the TXA group than in the non‐TXA group, but there was no statistical difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%